Three-dimensional macroporous structure iridium oxide material constructed by nano-particles and preparation and application of three-dimensional macroporous structure iridium oxide material

By constructing a three-dimensional macroporous structure in IrO2 catalyst, using polymer template method and amphiphilic triblock copolymer, the problems of insufficient catalytic activity and reduced reaction rate are solved, and efficient electrocatalytic performance and electrochemistry of water oxidation are achieved stability.

CN119461520APending Publication Date: 2025-02-18TONGJI UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411589751.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In large-scale applications, existing IrO2 catalysts have problems such as insufficient catalytic activity, limited specific surface area, insufficient exposure of catalytic active sites, and reduced reaction rate and decay under industrial high current conditions.

Method used

Through rational design and optimization of the preparation process, the polymer template method is used to combine amphiphilic triblock copolymer as surfactant to construct a three-dimensional macroporous IrO2 nanomaterial with continuous rich pore channels and nanoroughened pore walls.

Benefits of technology

The high specific surface area and large pore volume ratio of the catalyst are achieved, more catalytic active sites are provided, mass transfer and diffusion of reactants and products are improved, and the mechanical strength and electrochemical stability of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461520A_ABST
    Figure CN119461520A_ABST
Patent Text Reader

Abstract

The invention relates to a three-dimensional macroporous structure iridium oxide material constructed by nanoparticles and preparation and application thereof, the iridium oxide material is prepared by the following method: (1) dissolving an iridium salt precursor reagent in deionized water to prepare an iridium salt precursor solution, and then adding an amphiphilic triblock copolymer; (2) ultrasonically dispersing a polymer template agent into deionized water to prepare a template agent emulsion; (3) uniformly mixing the iridium salt precursor / amphiphilic triblock copolymer mixed solution with the template agent emulsion, and drying at a constant temperature; and (4) performing high-temperature calcination in an oxygen atmosphere to obtain the three-dimensional macroporous structure material constructed by the iridium oxide nanoparticles. The nanoparticle and three-dimensional macroporous structure compounded iridium oxide material disclosed by the invention has the advantages of excellent catalytic activity, stability and the like when being applied to electrolytic water decomposition as a water oxidation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis catalyst materials and relates to a three-dimensional macroporous iridium oxide material constructed with nanoparticles and the preparation and application thereof. Background Art

[0002] Since the 21st century, the global demand for energy has continued to grow, and the concern for the environment has also deepened. Although traditional fossil energy such as coal, oil and natural gas have played an important role in promoting industrial development and meeting human life needs, their non-renewable nature and the production of greenhouse gases such as carbon dioxide after combustion have led to problems such as resource depletion and environmental degradation. Therefore, the development of clean and renewable energy has become a key way to solve the global energy crisis and environmental problems. Hydrogen energy is considered to be one of the most promising clean energy sources in the 21st century. Due to its high energy density, flexible utilization, clean and pollution-free, and the ability to couple with a variety of energy sources, it occupies an important position in the low-carbon energy transition. Among various hydrogen production methods, water electrolysis technology has attracted widespread attention and attention from the industry because of its simple operation, high product purity, easy distributed layout, and the ability to use renewable energy to generate electricity. Compared with traditional alkaline (ALK) water electrolysis technology, proton exchange membrane (PEM) water electrolysis technology has the advantages of higher hydrogen purity (≥99.99%), smaller size, faster response, and better self-consistent renewable energy volatility. It is an important direction for the development of water electrolysis technology in the future.

[0003] Compared with the hydrogen evolution reaction, the oxygen evolution reaction involves a complex 4e - / 4H + The transfer process and the OO bond formation step have high overpotential and slow kinetics, becoming the bottleneck half-reaction of water decomposition to produce hydrogen. Therefore, it is urgent to develop electrocatalysts with excellent performance to reduce the reaction energy barrier, thereby reducing the energy consumption and economic cost of large-scale water electrolysis. As a precious metal oxide, iridium oxide (IrO2) exhibits excellent catalytic activity and electrochemical stability in the electrocatalytic water oxidation process due to its high conductivity, corrosion resistance and stability under strong acidic conditions. It is considered to be the most effective water oxidation electrocatalyst for PEM water electrolysis. However, there are still some problems in the practical application of IrO2 materials. First, IrO2 itself is a precious metal oxide, and its large-scale application requires further improvement of its catalytic activity and atomic utilization. Secondly, traditional IrO2 catalysts are usually disordered nanoparticle stacking structures. Although this structure has certain catalytic activity, its specific surface area is limited and the catalytic active sites are insufficiently exposed, thereby reducing the overall catalytic efficiency. In addition, in the electrocatalytic process, especially under industrial high current conditions, the mass transfer of reactants and products is limited, which will cause a decrease in reaction rate and catalyst activity decay.

[0004] In view of these problems, the development of a three-dimensional macroporous IrO2 catalyst material with a high roughness surface is a potential solution. However, there is currently a lack of a simple and efficient preparation method to construct a three-dimensional macroporous IrO2 nanomaterial with continuous and rich pores and nano-roughened pore walls. The present invention is proposed based on this. Summary of the invention

[0005] The purpose of the present invention is to provide a three-dimensional macroporous iridium oxide material constructed by nanoparticles and its preparation and application.

[0006] The applicant has found through research that three-dimensional macroporous structure catalysts have many advantages: i) The pore size of the macroporous structure is adjustable, which can effectively increase the specific surface area of ​​the catalyst and expose more active sites, thereby improving the overall catalytic performance of the catalyst. ii) The macroporous channel facilitates the rapid transfer and diffusion of reactants and products, especially reducing mass transfer resistance under industrial high current conditions, thereby improving catalytic efficiency. iii) The construction of a three-dimensional continuous structure can form a continuous conductive channel and reduce polarization resistance. iv) The construction of a three-dimensional continuous structure can also enhance the mechanical strength of the material and increase the structural stability of the catalyst, thereby extending its service life. v) In particular, a three-dimensional macroporous structure catalyst whose pore walls are composed of nanoparticles has a more significant advantage. Nanoparticles can provide more active sites and increase the reaction rate through their high specific surface area.

[0007] However, the preparation of relevant catalysts in practical applications still faces many challenges. In particular, the construction of three-dimensional macroporous IrO2 nanomaterials with continuous and rich pores and nano-roughened pore walls requires the coordination and consideration of multiple factors, such as the structural stability of the three-dimensional macropores, the controllability of the pore size, the nano-roughening of the pore walls, and the valence state regulation from Ir(0) to IrO2. For example, the glass transition temperature and decomposition temperature of the polymer template need to be well matched with the decomposition temperature of the iridium salt precursor in order to form a continuous pore structure; for another example, the use of specific surfactants may be necessary for the nano-roughening of the pore walls, and it is also required that they can be decomposed and disappeared during the calcination and preparation of the catalyst. On the other hand, due to the huge differences in their structural properties, the compatibility and effectiveness of different surfactants in specific systems need to be studied in depth; for another example, due to the high surface energy of nanoparticles, they are prone to agglomeration during the preparation process, which challenges the formation and stability of continuous pore walls.

[0008] In order to solve the problems found in the above research process, the present invention constructs a three-dimensional macroporous IrO2 nanomaterial with rich continuous pores and nano-roughened pore walls through reasonable design and optimization of the preparation process; the three-dimensional macroporous structure iridium oxide material constructed by the provided nanoparticles is applied to the water oxidation reaction of electrolysis of water to produce hydrogen, and exhibits excellent catalytic performance, and is expected to play an important role in future energy technologies and provide important technical support for solving current energy and environmental problems.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] One of the purposes of the present invention is to provide a method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles, comprising the following steps:

[0011] (1) dissolving an iridium salt precursor reagent in deionized water to obtain an iridium salt precursor solution, and then adding an amphiphilic triblock copolymer as a surfactant to obtain an iridium salt precursor / amphiphilic triblock copolymer mixed solution after dissolution;

[0012] (2) ultrasonically dispersing the polymer template in deionized water to prepare a template emulsion;

[0013] (3) mixing the iridium salt precursor / amphiphilic triblock copolymer mixed solution and the template agent emulsion uniformly, and drying at a constant temperature to obtain a block solid mixture filled with the iridium precursor;

[0014] (4) The bulk solid mixture filled with the iridium precursor is calcined at a high temperature in an oxygen atmosphere to obtain a three-dimensional macroporous structure material constructed by iridium oxide nanoparticles.

[0015] Furthermore, in step (1), the iridium salt precursor reagent is any one of iridium acetate and iridium acetylacetonate.

[0016] Furthermore, in step (1), the amphiphilic triblock copolymer is any one of P123 and F127.

[0017] Furthermore, in step (1), the mass ratio of the amphiphilic triblock copolymer to the iridium salt precursor reagent is 1:3-50.

[0018] Furthermore, in step (1), the mass concentration of the iridium salt precursor solution is 2% to 15%.

[0019] Furthermore, in step (2), the polymer template is any one of spherical PS and PMMA, and the spherical diameter thereof is 100 to 500 nm.

[0020] Furthermore, in step (2), the mass concentration of the polymer template is 10 to 50 mg / ml.

[0021] Furthermore, in step (3), the added amounts of the iridium salt precursor / amphiphilic triblock copolymer mixed solution and the template emulsion satisfy the following conditions: the mass ratio of the polymer template to the iridium salt precursor reagent is 4 to 10:1.

[0022] Furthermore, in step (3), the temperature of the constant temperature drying is 60 to 90° C., and the time is 6 to 12 hours.

[0023] Furthermore, in step (4), the calcination temperature is 350-600° C. and the calcination time is 0.5-3 h.

[0024] Furthermore, in step (4), the calcination atmosphere is an oxygen atmosphere.

[0025] The second object of the present invention is to provide a three-dimensional macroporous iridium oxide material constructed by nanoparticles, which is prepared based on the preparation method described in any one of the above items.

[0026] The third purpose of the present invention is to provide a three-dimensional macroporous structure iridium oxide material constructed by nanoparticles for use as a water oxidation electrocatalyst in water electrolysis.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) The present invention successfully prepared a three-dimensional macroporous iridium oxide material constructed by nanoparticles by combining an amphiphilic triblock copolymer as a surfactant, which can be used as an efficient water oxidation electrocatalyst for electrolysis of water and oxygen evolution. This unique zero-dimensional nano- and three-dimensional macroporous composite structure has the advantages of high specific surface area and macropore volume ratio, can provide more catalytic active sites, and is conducive to the mass transfer and diffusion of reactants and products.

[0029] (2) The iridium oxide prepared by the present invention has higher catalytic activity and stability than existing similar water oxidation electrocatalysts. When used as a water oxidation electrocatalyst, the IrO2 catalyst drop-coated on the glassy carbon electrode can generate 10 mA cm at only 290 mV in a 0.5 M H2SO4 solution. –2 In addition, the catalyst was made into a membrane electrode and the catalytic current density was 1A / cm 2 Under the current density condition, there was no obvious attenuation after long-term electrolysis for 100 h, indicating that the catalyst has good electrochemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD pattern of the prepared three-dimensional macroporous IrO2;

[0031] Figure 2 The SEM image of the prepared three-dimensional macroporous IrO2;

[0032] Figure 3 This is a SEM image of IrO2 obtained by direct calcination of iridium salt;

[0033] Figure 4 The SEM image of three-dimensional macroporous IrO2 prepared without using amphiphilic triblock copolymer;

[0034] Figure 5 is the SEM image of IrO2 prepared using excess amphiphilic triblock copolymer;

[0035] Figure 6 SEM images of IrO2 prepared by changing the particle size (100 nm) of the polymer template PMMA;

[0036] Figure 7 XRD patterns of materials obtained by changing the calcination atmosphere (air);

[0037] Figure 8 XRD patterns of materials obtained by changing the calcination atmosphere (nitrogen);

[0038] Fig. 9 The LSV curves of electrocatalytic water oxidation of iridium-based materials prepared under different polymer template and amphiphilic triblock copolymer addition conditions;

[0039] Fig.10 The Tafel curves of electrocatalytic water oxidation of iridium-based materials prepared under different polymer template and amphiphilic triblock copolymer addition conditions;

[0040] Fig.11 The LSV curves of electrocatalytic water oxidation of iridium-based materials prepared under different atmosphere conditions;

[0041] Fig.12 For three-dimensional macroporous IrO2 materials at 1A / cm 2 Electrolysis curve under current density conditions. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0043] In the following examples, PMMA (polymethyl methacrylate) template was synthesized in the laboratory by conventional solution polymerization:

[0044] Add 200 ml of deionized water to a three-necked flask, heat to 70°C in a water bath, and introduce nitrogen into the solution for 30 minutes to remove dissolved oxygen; add 0.106 g of potassium persulfate, stir magnetically for 5 minutes, then add 15.3 ml of MMA (methyl methacrylate) monomer to the reaction vessel, and react at 70°C for 1 hour under nitrogen atmosphere. After the reaction is completed, a white PMMA emulsion is obtained.

[0045] The emulsion obtained by the above reaction was centrifuged (10000rpm, 8min), and then washed repeatedly with deionized water for 3 times to remove the unreacted organic small molecules, potassium persulfate and impurities. Finally, the solid obtained by centrifugation was dried for standby use, and the diameter of the prepared PMMA nanospheres was 200nm. PMMA nanospheres of different particle sizes can be obtained by regulating the ratio of initiator potassium persulfate, the dropping speed of MMA and the reaction temperature.

[0046] PS (polystyrene) template, amphiphilic triblock copolymer P123 (chemical formula PEO-PPO-PEO, molecular weight 5800), and F127 (chemical formula PEG-PPG-PEG, molecular weight 12600) were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0047] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0048] Embodiment 1:

[0049] Dissolve 50 mg of iridium acetate in 2 ml of deionized water, then take 10 mg of amphiphilic triblock copolymer P123 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water, and disperse evenly to form solution B; after ultrasonic mixing, place solution A and solution B in an 80-degree oven for heating and drying to obtain a block solid uniformly filled with iridium salt precursor. Finally, put the above solid into a tube furnace, heat it to 450°C in an oxygen atmosphere, calcine it for 1 hour, and cool it to room temperature to obtain an IrO2 nanomaterial with a three-dimensional macroporous structure. As a control group, directly place iridium acetate in a tube furnace, heat it to 450°C in an oxygen atmosphere, calcine it for 1 hour, and cool it to room temperature to obtain an IrO2 nanomaterial with a disordered structure.

[0050] Figure 1 is the XRD pattern of the prepared material. It can be seen from the figure that the XRD diffraction peak of the prepared material corresponds to IrO2 (PDF#43-1019), and no other iridium species (such as metallic Ir) are found.

[0051] Figure 2The SEM image of the prepared sample material is shown. The structural characterization and analysis of the material show that the prepared sample material has a three-dimensional interconnected porous structure with a uniform pore structure and a pore size of about 180nm. At the same time, it can be found that there are a large number of nanoparticles on the three-dimensional macroporous framework structure.

[0052] The above XRD and SEM results show that a three-dimensional macroporous IrO2 material constructed by nanoparticles has been successfully prepared. Figure 3 The morphology of the material prepared by direct calcination of iridium acetate (the morphology of the material prepared by mixed calcination of iridium acetate and amphiphilic triblock copolymer) Figure 3 similar), the material has a uniform macroporous structure ( Figure 2 ) will provide convenient channels for the transfer of substances and diffusion of gases during the electrocatalytic water oxidation process; in addition, the nanoparticle microstructure of the pore wall of the macroporous structure can provide more catalytic active sites for electrocatalytic water oxidation.

[0053] The present invention selects the amphiphilic triblock copolymer as a surfactant, mainly based on the following two considerations: first, the surfactant is solid at room temperature, which matches the experimental conditions (drying step) for constructing the nano-roughened macroporous structure of the present invention; second, the surfactant is easy to form ionic micelles with the inorganic metal salt solution in the system after dissolution, thereby constructing nanoparticles. For example, liquid surfactants (such as Triton X-100) at room temperature exist in the form of high-boiling liquids, and a dry solid mixture cannot be obtained during the drying process for subsequent calcination, and ultimately a three-dimensional macroporous structure cannot be obtained, so it is not suitable for the preparation method of the present invention.

[0054] Embodiment 2:

[0055] Dissolve 50 mg of iridium acetate in 2 ml of deionized water to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water and disperse evenly to form solution B; ultrasonically mix solution A and solution B, place them in an 80-degree oven for heating and drying, and obtain a block solid uniformly filled with iridium salt precursor. Finally, place the above solid in a tubular furnace, heat to 450°C in an oxygen atmosphere, calcine for 1 hour, and cool to room temperature to obtain an IrO2 nanomaterial with a three-dimensional macroporous structure.

[0056] Figure 4 The SEM image of the prepared sample material is shown, and the structural characterization and analysis of the prepared material show that although the prepared sample material has a three-dimensional interconnected porous structure, since no amphiphilic triblock copolymer is added as a surfactant, the surface of the three-dimensional macroporous framework structure is smooth and there is no rough nanoparticle structure.

[0057] Embodiment 3:

[0058] Dissolve 50 mg of iridium acetate in 2 ml of deionized water, then take 100 mg of excess amphiphilic triblock copolymer P123 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water, and disperse evenly to form solution B; ultrasonically mix solution A and solution B, and place them in an 80-degree oven for heating and drying to obtain a block solid uniformly filled with iridium salt precursor. Finally, place the above solid in a tubular furnace, heat to 450°C in an oxygen atmosphere, calcine for 1 hour, and cool to room temperature to obtain IrO2 nanomaterials.

[0059] Figure 5 The SEM image of the prepared sample material is shown. The structural characterization and analysis of the prepared material show that although the prepared sample material has a rich nanoparticle structure, due to the use of excessive amphiphilic triblock copolymer as a surfactant, the pore structure of the material is severely damaged and a three-dimensional macroporous structure cannot be formed.

[0060] Embodiment 4:

[0061] Dissolve 50 mg of iridium acetate in 2 ml of deionized water, then take 10 mg of amphiphilic triblock copolymer P123 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 100 nm in deionized water, and disperse evenly to form solution B; ultrasonically mix solution A and solution B, and place them in an 80-degree oven for heating and drying to obtain a block solid uniformly filled with iridium salt precursor. Finally, place the above solid in a tubular furnace, heat to 450°C in an oxygen atmosphere, calcine for 1 hour, and cool to room temperature to obtain IrO2 nanomaterials.

[0062] Figure 6 The SEM image of the prepared sample material is shown, and the structural characterization and analysis of the prepared material show that the prepared sample material has a three-dimensional interconnected porous structure, a uniform pore structure, and a pore size of about 90nm. At the same time, it can be found that there are a large number of nanoparticles on the three-dimensional macroporous framework structure. Combining Example 1 (200nm polymer template PMMA) and Example 4 (100nm polymer template PMMA), the above results show that the pore size of the three-dimensional macroporous material can be effectively regulated by changing the particle size of the polymer template. It should be pointed out that the particle size of the spherical polymer template should be moderate. Too large a particle size can easily lead to insufficient filling, and too small a particle size can easily lead to clogging of the holes.

[0063] Embodiment 5:

[0064] Dissolve 50 mg of iridium acetate in 2 ml of deionized water, then take 10 mg of P123 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water, and disperse evenly to form solution B; after ultrasonically mixing solution A and solution B, place them in an oven at 80 degrees for heating and drying to obtain a block solid uniformly filled with iridium salt. Finally, place the above solid in a tubular furnace, heat it to 450°C in an air atmosphere, calcine it for 1 hour, and cool it to room temperature to obtain iridium-based nanomaterials.

[0065] Figure 7 is the XRD diagram of the prepared material. It can be seen that the XRD diffraction peaks of the prepared material correspond to metallic iridium (PDF#41-0600) and iridium oxide (PDF#43-1019), respectively, proving that the prepared sample is a composite material of metallic iridium and iridium oxide.

[0066] Embodiment 6:

[0067] Dissolve 50 mg of iridium acetate in 2 ml of deionized water, then take 10 mg of P123 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water, and disperse evenly to form solution B; after ultrasonically mixing solution A and solution B, place them in an 80-degree oven for heating and drying to obtain a block solid uniformly filled with iridium salt. Finally, place the above solid in a tubular furnace, heat it to 450°C in an N2 inert gas atmosphere, calcine it for 1 hour, and cool it to room temperature to obtain iridium-based nanomaterials.

[0068] Figure 8 The XRD diagram of the prepared material shows that, due to the use of N2 inert gas atmosphere for calcination, the XRD diffraction peak of the prepared material corresponds to metallic iridium (PDF#41-0600), and there is basically no iridium oxide substance. Based on the comparison of Example 1, Example 5 and Example 6, it can be predicted that by controlling the calcination atmosphere, this experimental method can achieve continuous regulation from Ir(0) to Ir(0) / IrO2 mixture to IrO2.

[0069] Embodiment 7:

[0070] The IrO2 material prepared in Example 1 and Example 2 was used as a water oxidation catalyst to prepare a working electrode, and the specific steps were as follows:

[0071] The electrocatalytic water oxidation performance was tested in a three-electrode electrolytic cell. The working electrode was a glassy carbon electrode loaded with IrO2 catalyst material, the counter electrode was a platinum wire, and the reference electrode was a saturated calomel electrode. The electrocatalytic performance was tested in a 0.5M H2SO4 solution saturated with N2, and the test curve was not ohm-compensated. The scan rate of the LSV test was 100mV s –1 , the experimental test temperature is 25±2℃.

[0072] Preparation method of working electrode: Use a pipette to absorb 5μl of 20wt% Nafion solution and disperse it into 1ml of a mixed solution of deionized water and ethanol (volume ratio is 4:1). Use an analytical balance to weigh 4mg of the prepared catalyst material, and then ultrasonically disperse the catalyst material evenly in the mixed solution of water and ethanol; Take 5μl of the catalyst slurry and drop it on a glassy carbon electrode with a diameter of 3mm, and use it as a working electrode after drying naturally.

[0073] like Fig. 9 As shown in the figure, the three-dimensional macroporous IrO2 material prepared by PMMA and P123 produces 10 mA cm –2 When the catalytic current density is 290 mV, the required overpotential is 290 mV, which is relatively higher than that of the control group (the control group in Example 1 has no P123 and PMMA added, i.e. Figure 3 The material prepared by direct calcination of iridium acetate; and Example 2 without the addition of P123, i.e. Figure 4 The prepared material shown in FIG. ) exhibits high electrocatalytic water oxidation activity, and its catalytic performance is comparable to or better than that of various types of high-quality iridium oxide catalysts reported so far.

[0074] Fig.10 The Tafel curve shows that the Tafel slope of the three-dimensional macroporous IrO2 prepared by PMMA and P123 is 67 mV dec. –1 , indicating that the three-dimensional macroporous IrO2 catalytic electrode has excellent electrocatalytic water oxidation reaction kinetic characteristics compared with the control samples.

[0075] Embodiment 8:

[0076] The iridium-based material prepared in Example 6 was used as a water oxidation catalyst to prepare a working electrode, and the specific steps were as follows:

[0077] The electrocatalytic water oxidation performance was tested in a three-electrode electrolytic cell. The working electrode was a glassy carbon electrode loaded with iridium-based catalyst material, the counter electrode was a platinum wire, and the reference electrode was a saturated calomel electrode. The electrocatalytic performance was tested in a 0.5M H2SO4 solution saturated with N2, and the test curve was not ohm-compensated. The scan rate of the LSV test was 100mV s – 1 , the experimental test temperature is 25±2℃.

[0078] Preparation method of working electrode: Use a pipette to absorb 5μl of 20wt% Nafion solution and disperse it into 1ml of a mixed solution of deionized water and ethanol (volume ratio is 4:1). Use an analytical balance to weigh 4mg of the prepared catalyst material, and then ultrasonically disperse the catalyst material evenly in the mixed solution of water and ethanol; Take 5μl of the catalyst slurry and drop it on a glassy carbon electrode with a diameter of 3mm, and use it as a working electrode after drying naturally.

[0079] like Fig.11 As shown in the figure, compared with the three-dimensional macroporous IrO2 material prepared under oxygen atmosphere, the iridium-based catalyst prepared under inert nitrogen atmosphere showed poor electrocatalytic water oxidation activity. At the same time, under low potential conditions, the metal iridium catalyst showed an obvious oxidation peak, which was attributed to the surface oxidation process of the metal iridium catalyst.

[0080] Embodiment 9:

[0081] The IrO2 material prepared in Example 1 was used as the anode water oxidation catalyst, commercial 20wt% Pt / C was used as the cathode water reduction catalyst, and Nafion 115 was used as the proton exchange membrane intermediate layer. The membrane electrode was prepared by conventional ultrasonic spraying. The specific steps were as follows:

[0082] 5 μl of 20 wt% Nafion solution was dispersed into 1 ml of a mixed solution of deionized water and isopropanol (volume ratio of 1:1) using a pipette; a certain amount of the prepared IrO2 catalyst material was weighed using an analytical balance, and then the catalyst material was evenly dispersed in the mixed solution by ultrasonication; the catalyst slurry was sprayed onto one side of the Nafion proton exchange membrane using an ultrasonic spraying method, and the catalyst loading was 0.8 mg Ir / cm 2 The Pt / C catalyst on the other side of the membrane electrode was prepared by spraying according to the above steps, and the catalyst loading was 0.2 mg Pt / cm 2 .

[0083] Fig.12 The chronopotentiometry curve of the prepared membrane electrode shows that the catalyst has a high current density of 1A / cm 2 Under the condition of temperature of 60℃, the driving voltage required for the electrolytic cell is 1.745V, and there is no activity decay after long-term electrolysis for 100h, showing high potential for commercial application.

[0084] Embodiment 10:

[0085] Dissolve 50 mg of iridium acetylacetonate in 2 ml of deionized water, then take 10 mg of amphiphilic triblock copolymer P123 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water, and disperse evenly to form solution B; ultrasonically mix solution A and solution B, and place them in an 80-degree oven for heating and drying to obtain a mixed block solid. Finally, put the above solid into a tube furnace, heat it to 350°C in an oxygen atmosphere, calcine it for 3 hours, and cool it to room temperature to obtain an IrO2 nanomaterial with a three-dimensional macroporous structure.

[0086] Embodiment 11:

[0087] Dissolve 50 mg of iridium acetate in 2 ml of deionized water, then take 10 mg of amphiphilic triblock copolymer F127 and dissolve it in the above solution to form solution A; disperse 0.2 g of polymer template PMMA with a particle size of 200 nm in deionized water, and disperse evenly to form solution B; ultrasonically mix solution A and solution B, and place them in an oven at 80 degrees for heating and drying to obtain a mixed block solid. Finally, put the above solid into a tube furnace, heat it to 600°C in an oxygen atmosphere, calcine it for 0.5 hours, and cool it to room temperature to obtain an IrO2 nanomaterial with a three-dimensional macroporous structure.

[0088] Embodiment 12:

[0089] Dissolve 50mg of iridium acetate in 2ml of deionized water, then take 10mg of amphiphilic triblock copolymer P123 and dissolve it in the above solution to form solution A; disperse 0.2g of polymer template PS with a particle size of 200nm in deionized water, and disperse evenly to form solution B; ultrasonically mix solution A and solution B, and place them in an oven at 80 degrees for heating and drying to obtain a mixed block solid. Finally, put the above solid into a tube furnace, heat it to 600℃ in an oxygen atmosphere, calcine it for 0.5h, and cool it to room temperature to obtain IrO2 nanomaterials with a three-dimensional macroporous structure.

[0090] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a three-dimensional macroporous iridium oxide material constructed of nanoparticles, characterized in that: The following steps are involved: (1) dissolving an iridium salt precursor reagent in deionized water to obtain an iridium salt precursor solution, and then adding an amphiphilic triblock copolymer to obtain an iridium salt precursor / amphiphilic triblock copolymer mixed solution after dissolution; (2) ultrasonically dispersing the polymer template in deionized water to prepare a template emulsion; (3) mixing the iridium salt precursor / amphiphilic triblock copolymer mixed solution and the template agent emulsion uniformly, and drying at a constant temperature to obtain a block solid mixture filled with the iridium precursor; (4) The bulk solid mixture filled with the iridium precursor is calcined at a high temperature in an oxygen atmosphere to obtain a three-dimensional macroporous structure material constructed by iridium oxide nanoparticles.

2. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (1), the iridium salt precursor reagent is any one of iridium acetate and iridium acetylacetonate.

3. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (1), the amphiphilic triblock copolymer is any one of P123 and F127.

4. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (1), the mass ratio of the amphiphilic triblock copolymer to the iridium salt precursor reagent is 1:3-50.

5. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (2), the polymer template is any one of spherical PS and PMMA, and the spherical diameter thereof is 100 to 500 nm.

6. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (3), the added amounts of the iridium salt precursor / amphiphilic triblock copolymer mixed solution and the template emulsion satisfy the following conditions: the mass ratio of the polymer template to the iridium salt precursor reagent is 4 to 10:

1.

7. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (3), the temperature of the constant temperature drying is 60 to 90° C. and the time is 6 to 12 hours.

8. The method for preparing a three-dimensional macroporous iridium oxide material constructed by nanoparticles according to claim 1, characterized in that: In step (4), the calcination temperature is 350-600° C. and the calcination time is 0.5-3 h.

9. A three-dimensional macroporous iridium oxide material constructed of nanoparticles, characterized in that: It is prepared based on the preparation method according to any one of claims 1 to 8.

10. Use of the three-dimensional macroporous iridium oxide material constructed by nanoparticles as claimed in claim 9 as a water oxidation electrocatalyst in water electrolysis.

Citation Information

Cited By

  • A precursor-induced morphology-regulated iridium oxide electrocatalyst and a preparation method thereof

    CN122667647A